2023
DOI: 10.1186/s13018-023-04038-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the results of open PLIF versus UBE PLIF in lumbar spinal stenosis: postoperative adjacent segment instability is lesser in UBE

Abstract: Objective To compare the difference in efficacy between open PLIF and UBE for lumbar spinal stenosis and the effect on postoperative adjacent segment instability. Method The clinical data of 37 patients with PLIF and 32 patients with UBE for lumbar spinal stenosis were retrospectively analyzed to compare the differences in perioperative conditions and short- and medium-term outcomes. Results All 69 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…A total of 568 studies were omitted from the remaining 1128 due to their non-compliance with the study’s objectives, such as their classification as non-original research articles, and so on. The remaining 560 studies underwent a comprehensive text evaluation, which led to the exclusion of 479 studies, and 25 studies that satisfied the inclusion criteria 5 - 29 were included. To ensure the integrity of the data, a screening of included studies in recent UBE reviews 30 - 33 and identified 4 additional studies that were subsequently incorporated into this research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 568 studies were omitted from the remaining 1128 due to their non-compliance with the study’s objectives, such as their classification as non-original research articles, and so on. The remaining 560 studies underwent a comprehensive text evaluation, which led to the exclusion of 479 studies, and 25 studies that satisfied the inclusion criteria 5 - 29 were included. To ensure the integrity of the data, a screening of included studies in recent UBE reviews 30 - 33 and identified 4 additional studies that were subsequently incorporated into this research.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, a suggestion from Li has been put out to relocate the portals of the UBE-PLIF approach outward. 29 Unfortunately, Li’s study does not include details about the position used for the endoscope and working portals, and the account only mentions the pedicle as the anatomical reference. 29 Nevertheless, it is essential to acknowledge that the UBE-PLIF approach, which involves moving the incision outward, is increasingly gaining favor among surgeons.…”
Section: Resultsmentioning
confidence: 99%
“…The common lumbar degenerative diseases are lumbar disc herniation, lumbar spinal stenosis, lumbar spondylolisthesis, scoliosis and so on [ 2 ]. At present, for lumbar degenerative diseases, patients with mild clinical symptoms are mainly treated with conservative treatment, but for lumbar degenerative diseases with severe pain, long-term conservative treatment is ineffective, seriously affect daily life, often need surgical treatment [ 3 ]. Lumbar fusion surgery is considered to be an effective treatment, which can significantly improve patients' symptoms such as low back and leg pain, and improve their quality of life [ 4 ].…”
Section: Introductionmentioning
confidence: 99%